LANGKAH SUKSES BUDIDAYA PISANG KEPOK KUNING (Musa paradisiaka) BEBAS PENYAKIT MELALUI KULTUR JARINGAN SAMPAI LAPANGAN DAN PENGOLAHAN HASIL PANENNYA DI PROVINSI KALIMANTAN TIMUR - Ratna Nirmala; Ratna Shanti; Suyadi Suyadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
This research was a solution to free desease banana kepok yellow which was decrease the banana product in East Kalimantan. This research were devided three years and it would be continued. The first years seedling propagation free desease through tissue culture. The second years the seedling derived tissue culture which was planted on the field, until harvesting fruit product. The third years processing fruit product to several kind of industrial product. The aim of the first years research was the highest number shoot regenerated from the explant center of banana corm, which induction several combination treatment of plant growth regulator Benzyl Amino Purine (BAP) and Indole Butyric Acid (IBA). This research conducted at Tissue Culture Laboratory of Agriculture Faculty of Mulawarman University, from March until November 2015. This research was used Randomized Completely Block Design with two factors. The firest factor : BAP consist 3 level consentration were : 2,5; 5 and 10 ppm and the secon factor : IBA consist 3 level consentration were : 0; 1 and 2 ppm. So that all of combination of plant growth  regulator were 9 treatments. Each treatments were replicated ten times. Result of this research showed that all combination of concentration treatment of plant growth regulator BAP and IBA could be induce the growth and differentiation of explant center of banana corm in Murashige and Skoog (MS) media, like : inbibition, developed tissue of explant, callusing and shooting, although the percentage and totality was variation. The colour of callus was yellow and light green. While the structure was hard and compact. The highest average number of shoots induction at VII combination treatments BAP 10 ppm + IBA 0 ppm ware 3.80± 1,76 shoots/explant which was the root un completely development. So that it need sub culture to the rooting induction media with IBA 10 ppm to be formed completely plantlet (seedling), which could be survived on acclimatization processing.